The Sage handbook of new urban studies - Hannigan, John; Richards, Gred (Thousand Oaks, CA : SAGE Inc, 2017)
The last two decades have been an exciting and richly productive period for debate and academic research on the city. The SAGE Handbook of New Urban Studies offers comprehensive coverage of this modern re-thinking of urban theory, both gathering together the best of what has been achieved so far, and signalling the way to future theoretical insights and empirically grounded research.
Description based on MARC record for print version.
Keywords: Sociology, Urban -- Handbooks, manuals, etc; Cities and towns -- Handbooks, manuals, etc